Governance and Organizational Performance in the Era of Local and Regional Authorities in Sub-Saharan Africa: the Case of Cameroonian Municipalities - Nya, Magloire Tchatchoua; Kemgni, Georgette Moyum; Djeudja, Rovier; Tzegouo, Marie Alvisse; Messie, Thierry (Copernican Journal of Finance & Accounting, 2024)
The aim of this study is specially to evaluate the effect of the governancestructures, the functioning of governance bodies, the characteristics of non-conventionalgovernance actors and the non-conventional regulatory body at play in the municipalitieson the organisational performance in the context of decentralisation. Totest those four hypotheses, the study employs a quantitative analysis using the feasiblegeneralised least squares method panel data from the “GUICHET-Performance- PNDP”were cross-tabulated with the primary data relating to the independent variables, collectedby questionnaire. The results show that, unlike non-conventional practices,structural and conventional (regulatory) local governance practices have no effect onthe performance of organisations. These results, serve as a reminder to political leadersfor the urgent need for good practices and transparency in other to strengthen organisationalperformance at local levels. The results of this research also confirm theimportance of institutional bodies establishing a vigorous policy in support of decentralisation. Such a policy would contribute to improving decentralisation at all levels inCameroon.